La responsabilidad social empresarial en la economía global (2013)
The objective of this paper is to show why an important issue in international business and foreign trade has not been taken into account by Latin American companies, in difference of the European companies are putting into practice CSR in their business strategies. The relationship between CSR and financial performance is examined using a new methodology. The average age of the company is highly correlated with the ranking of social responsibility that they have. After this analysis, it appears that there is some correlation between CSR and financial performance of companies.